Mental fatigue delays visual search behaviour in young cyclists when negotiating complex traffic situations: A study in virtual reality. (October 2021) - Zeuwts, Linus H.R.H.; Iliano, Evelien; Smith, Mitchell; Deconinck, Frederik; Lenoir, Matthieu
Highlights: Child cyclists are more accident prone at the end of the school day 2. Mental fatigued young cyclists tend to cope differently with traffic situations 3. When cycling in a VR simulator, fatigued cyclists show delayed perception 4. Mental fatigue did not result in higher crash rates when cycling in VR. Abstract: Introduction: Mental fatigue has been shown to negatively affect motor and sport performance. To date, however, no research focused on assessing the effects of mental fatigue on hazard perception in young cyclists who are highly vulnerable in traffic, especially after school. Therefore, the purpose of this study was to examine the influence of induced mental fatigue on hazard perception and anticipation in young cyclists using a novel Virtual Reality bicycle simulator. Methods: In this randomised, counterbalanced, cross-over investigation, forty-eight young cyclists cycled through a Virtual Environment (VE) in which they were confronted with eight simple and six complex traffic situations. Simple traffic situations are considered events including only one other actor can cause a dangerous situation while complex traffic situations include multiple actors than contribute to the dangerous situation. Half of the children were mentally fatigued using the Stroop colour-word task while the other half immediately started the VR hazard perception test. On the second test occasion, one month later, the other half of the group was mentally fatigued. Results: The results demonstrate that mentally fatigued cyclists fixated the relevant areas of interest (AOIs) in the simple and complex later and showed delayed response times for the complex hazards. Mental fatigue, however, did not alter the speed with which participants cycled through the virtual environment and did not change the hazard perception score. Conclusion: To our knowledge, this was the first study to investigate the effect of mental fatigue in young cyclists with an innovative VR hazard perception simulator. Due to increased mental fatigue, young cyclists might have experienced more episodes of fatigue-related mind-wandering and a deterioration of selective attention for the task at hand. This resulted in a less thorough visual inspection of the scene and delayed braking responses.